Fentanyl - Based Cardiac Anesthesia Provides Higher Recovery Compared with Morphine in Elective CABG Surgery Patients - AMK, Hasan; Niaz, Ahmed; S, Ahmed; MZ, Haider; MAAM, Kabir; SMAZ, Nine; A, Khan; MS, Hasan (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background : High-dose opioid anesthesia during cardiac surgery has been the mainstay of cardiacanesthesia for decades due to its ability to preserve hemodynamic stability and attenuate hormonal andmetabolic response to surgical stress. The hypothesis of this study is that the use of fentanyl as part of abalanced anesthetic would lead to improved patient health status and recovery during the first 3 daysafter cardiac surgery with CPB compared with morphine. Quality of recovery was assessed using theQoR-40 questionnaire administered preoperatively and daily on postoperative days 1–3. Hemodynamicvariables, duration of tracheal intubation, organ morbidities, intensive care unit (ICU) and hospitallength of stay were evaluated. Methods: This comparative randomized double blind study was conducted in the department ofcardiothoracic vascular anaesthesia and critical care of Apollo Hospitals,Dhaka on 100 patientsundergoing elective CABG. Study period was (January-July), 2019. The study was approved by theinstitutional review board, and informed consent was obtained from all subjects. One hundred patientspresenting for elective CABG surgery, between the ages of 18 and 79, were enrolled in the study. Exclusioncriteria included (1) concurrent valvular surgery or the presence of valvular disease, (2) reoperativeprocedures, (3) unstable angina or elevated cardiac enzymes within 48 hours of surgery, (4) morphine orfentanyl allergy, (5) the need for an intra-aortic balloon pump or inotropic agents preoperatively, (6)psychiatric or central nervous system disturbances precluding completion of the QoR-40. Results: Compared with patients given morphine, those receiving fentanyl had higher global QoR-40scores on postoperative days 1 (174.8 vs 162.5, P 0.001), 2 (175 vs 166.1, P 0.001), and 3 (178.1 vs 167.3,P 0.001). Differences between the groups were observed in the QoR-40 dimensions of emotional state,physical comfort, and pain . Postoperative visual analog scale pain scores, use of pain medication in theICU and surgical ward, and postoperative febrile reactions were reduced significantly in the fentanylgroup . No differences between the groups were noted in duration of tracheal intubation,ICU and hospitallength of stay, or postoperativecomplications. Conclusion: Continuous intravenous infusions of fentanyl have been used to provide intraoperativeanalgesia also give good-to-excellent postoperative analgesia furthermore early extubation and the qualityof postoperative recovery in cardiac surgical patients can be enhanced when fentanyl is used as part of abalanced anesthetic. JBSA 2020; 33(1): 28-35